Why are the numbers always only a derived quantity... Money and educational system (Theatrum historiae, 2011)
The author focuses on the criteria that are used for evaluation of educational system and its educational level. He controverts that using only a quantificational view is unmaintainable. 1) From the economic point of view: It is obvious that behind the numbers there are always decisions concerning their quantum and division. And we obtain the same situation when we count only with the quantification of the incomes of educational process. 2) It is necessary to take into consideration the time factor of this process too which is in the social level – in principle – generational. Efficiency, standards and forms of the education and educational system are basically derived from the time factor. 3) Moreover, the merits play an important, let ́s say crucial, role in the educational system (institutional or family) and these can not be essentially quantified.